Analisis Efektivitas Asupan Nutrisi Untuk Ibu Hamil dalam Mencegah Stunting - Ridwan, Heri; Sopiah, Popi; Aeni , Ira Nur; Putri , Jans Riva; Azhar, M. Raihan Fadhil; Aprilia, Puput Bela; Marsellina, Selly; Nofelinda, Shelfiana (Innovative: Journal Of Social Science Research, 2024)
Stunting is a condition of failure to thrive in toddlers characterized by below-standard height for their age. The main cause of stunting is chronic malnutrition which often starts during pregnancy. Inadequate nutritional intake from pregnant women has a major effect on fetal growth. Adequate nutrient intake, including calories, protein, vitamins and minerals, is essential to support fetal growth and prevent the risk of stunting. This study aims to analyze the effectiveness of nutritional intake for pregnant women in preventing stunting, taking into account various factors that affect maternal and child health. The methodology used in this research is a literature review. The literature sources used were Google Scholar and Semantic. Literature inclusion requirements include based on the title, keywords Nutrition, Pregnant women, Stunting, abstract suitability, full text review, and finally quality evaluation to assess the validity and reliability of each study that matches the topic to be discussed with the range of years 2019-2024. This study reveals the findings of the effectiveness of adequate nutritional intake in pregnant women and environmental factors such as lack of knowledge and lifestyle can affect the prevention of stunting risk in the fetus that will be born, with good macronutrient intake such as protein, Vitamins A, C, K, E and B complex, magnesium, iron, folic acid, fiber, energy, unsaturated fat, carbohydrates, fiber, calcium, iron, vitamins B1 & B2 can prevent stunting.  Nutritional supplementation for pregnant women is also significantly associated with newborn health, indicating that the nutritional status of the mother influences the fetus to be born without stunting.